Molecular Basis for the Adjuvant Potential of Nigella sativa–Derived Bioactive Constituents in Overcoming Resistance to Cancer Therapy - Nasywa Zahirah Yustin; Ghani Phalosa; Feby Anastasya Sirait (Institute of Advanced Knowledge and Science, 2026)
Resistance to cancer therapy remains a major cause of treatment failure, tumor recurrence, and disease progression because malignant cells can adapt through interconnected mechanisms involving prosurvival signaling, apoptosis suppression, drug efflux, epithelial–mesenchymal plasticity, cancer stemness, and the tumor microenvironment. This narrative review evaluates the molecular basis and adjuvant potential of Nigella sativa–derived bioactive constituents in overcoming resistance to conventional cancer therapies. Relevant literature was identified from Scopus, PubMed, Web of Science, ScienceDirect, and Google Scholar, with emphasis on resistance-related mechanisms, treatment sensitization, and combination-therapy studies. Among the identified constituents, thymoquinone has the strongest preclinical evidence. It modulates PI3K/Akt/mTOR, JAK/STAT, NF-κB, and Wnt/β-catenin signaling; enhances mitochondrial apoptosis; regulates ABC drug transporters; and influences autophagy, epithelial–mesenchymal transition, and cancer stem-cell properties. Thymoquinone has also enhanced the effects of chemotherapy, radiotherapy, and selected targeted agents in several experimental models, although treatment responses vary according to cancer type, dose, formulation, therapeutic combination, and microenvironmental conditions. Evidence for α-hederin, thymohydroquinone, dithymoquinone, thymol, and carvacrol remains comparatively limited, particularly in validated models of established treatment resistance. Clinical translation is further constrained by poor thymoquinone solubility and bioavailability, chemical instability, phytochemical variability, limited pharmacokinetic data, and insufficient evaluation of long-term safety and drug interactions. Overall, N. sativa-derived constituents, particularly thymoquinone, represent promising multi-target adjuvant candidates rather than alternatives to established cancer treatments. Future research should prioritize chemically standardized preparations, resistant cancer models, quantitative combination analyses, clinically relevant dosing, and well-designed pharmacokinetic, toxicological, and early-phase clinical studies.